Pengaruh Koagulan Biji Asam Jawa (Tamarindus indica) Terhadap Efisiensi Penurunan Zat Organik Pada Air Gambut - Vina Lestari Riyandini; Muhammad Iqbal (Fakultas Teknik, 2020)
Organic substances in peat water cause smell, have a brown color and taste, in addition to that it can interfere the processing process by forming carcinogenic trihalomethane which is produced from the reaction between organic compounds and chlorine. Peat water used in this study came from the village of Tuah Indrapura, Siak Regency with a concentration of organic matter of 95.2 mg/L. Based on Permenkes No. 492 of 2010 the concentration of organic substances exceeds the quality standard, so it needs to be treated before being used as a source of clean water. Therefore, in this study, uses the coagulation method of flocculation by utilizing natural coagulants, namely tamarind seeds (Tamarindus Indica). The study was conducted using variations in the size of biokoagulan by 200 mesh, 230 mesh, and 270 mesh with a dose variation of 1 gr, 2 gr, 3 gr, 4 gr dan 5 gr. The result showed that using 270 mesh biokoagulan particle size as much as 2 grams can set aside organic matter by 64%. This allowance is not large enough because tannins only form aggregates with organic substances in the form of proteins and alkaloids.